2003
DOI: 10.1200/jco.2003.01.199
|View full text |Cite
|
Sign up to set email alerts
|

Time Course and Predictors of Symptoms After Primary Prostate Cancer Therapy

Abstract: Pretreatment function and the primary treatment modality for early stage PC strongly predict the affected organ systems and time course of dysfunction. With this information, patients and their physicians may refine their choice of treatment and better anticipate its consequences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
137
0
1

Year Published

2008
2008
2012
2012

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 204 publications
(157 citation statements)
references
References 21 publications
19
137
0
1
Order By: Relevance
“…[6][7][8]11] External beam radiotherapy has not been found to cause incontinence in these studies, whereas evidence suggests that brachytherapy may impact urinary incontinence at low levels, whose clinical significance is uncertain. Brachytherapy and external beam radiotherapy have both been found to impact overall urinary functioning, with the principal impacted subdomain being urinary irritative/ obstructive symptoms, that are common during early follow-up after brachytherapy, and less common, but also detected, after external radiotherapy.…”
Section: Impact Of Primary Prostate Cancer Treatment On Specific Hrqomentioning
confidence: 75%
See 3 more Smart Citations
“…[6][7][8]11] External beam radiotherapy has not been found to cause incontinence in these studies, whereas evidence suggests that brachytherapy may impact urinary incontinence at low levels, whose clinical significance is uncertain. Brachytherapy and external beam radiotherapy have both been found to impact overall urinary functioning, with the principal impacted subdomain being urinary irritative/ obstructive symptoms, that are common during early follow-up after brachytherapy, and less common, but also detected, after external radiotherapy.…”
Section: Impact Of Primary Prostate Cancer Treatment On Specific Hrqomentioning
confidence: 75%
“…Valid, conclusive data regarding impact of brachytherapy on these HRQOL domains is limited to early follow-up (1 year or less). [6,11] The hormonal and vitality HRQOL domain, that has emerged as a significant component of HRQOL status among prostate cancer patients (due to increasing utilization of neoadjuvant hormonal therapy) has not been characterized in multicenter studies as of yet, though ongoing cohorts aim to address this knowledge gap.…”
Section: Impact Of Primary Prostate Cancer Treatment On Specific Hrqomentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous studies have shown that baseline HRQOL is a predictor of HRQOL after treatment. 17,18 However, we also observed a strong interaction between comorbidity and baseline HRQOL. To avoid overcorrection for a relevant aspect of comorbidity that impacts both baseline and future HRQOL, we elected to report our data without correction for baseline HRQOL, though we conducted all of our analyses with Comorbidity severity predicts HRQOL TJ Daskivich et al and without inclusion of baseline HRQOL as a covariate.…”
Section: Comorbidity Severity Predicts Hrqol Tj Daskivich Et Almentioning
confidence: 52%